Less of the Absolute, more of the pedagogical. Hans Blumenberg and education - Sosnowska, Paulina (Studia Philosophiae Christianae, 2019)
The aim of this article is to consider the philosophy of Hans Blumenberg as potentially pedagogical thought. Hans Blumenberg’s way of questioning can be juxtaposed with the Heideggerian way of questioning (much more popular in the philosophy of education) that starts with the human being as an ontologically distinguished creature. Blumenberg, unlike Heidegger, does not pursue the question of being as such, he consciously limits himself to anthropology, i.e. the humanity of being. Consequently, his anthropology is not fundamentally ontological, but contingent and culture-oriented. Blumenberg’s phenomenological description of humanity concentrates on the ways humans deal with different modes of the absolute (not only theological, but also natural and political). It is a consequence of Blumenberg’s anthropological statement concerning the human being as an underprivileged creature which compensates its natural shortcomings with culture (i.e. myths, metaphors, science, etc.), being able to make the absolute less predominant or rigorous, mitigating it in a way. This has humanistic and pedagogical import: the greater distance between us and absolute realities, the more space there is for human creativity and self-creativity, foremostly in the field of education.